Effect of neutron irradiation on microstructure and strength of Bi-2212 phase superconductor - Mohiju Z.A.; Mujaini M.; Hamid N.A.; Abdullah Y. (Institute of Physics Publishing, 2023)
Bismuth compounds; Calcite; Calcium carbonate; Copper oxides; Grain boundaries; Neutron sources; Nuclear reactors; Phase structure; Scanning electron microscopy; Solid state reactions; Superconducting materials; Sustainable development; X ray diffraction; Irradiated samples; Neutron irradiated; Phase formations; Physical strength; Porous structures; Radiation environments; Solid state reaction method; Superconducting phase; Neutron irradiation